Adolescent neurobehavioral characteristics, alcohol sensitivities, and intake: Setting the stage for alcohol use disorders? - Spear, Linda Patia (2011)
The transition to adolescence is characterized by rapid biological transformations that include not only the hormonal and physiological changes of puberty but also dramatic changes in the brain as well. Similar neural and physiological changes are associated with the transition from immaturity to maturity across a variety of mammalian species, along with a variety of common adolescent-typical behavioral characteristics. Among the neural systems undergoing alterations during adolescence are those that modulate sensitivity to a variety of alcohol effects, potentially increasing the propensity for relatively high levels of adolescent alcohol use, which in turn may set the stage for later alcohol use disorders. This article reviews research on adolescent alcohol sensitivities and suggests possible implications of these findings for the frequent initiation and relatively high levels of alcohol intake seen at this age.